Leadership in War and Peace : Masculine and Feminine - Johnson-Freese, Joan (Routledge, 2025)
This book offers a gendered perspective on leadership in war and peace, considering leadership in its complexity and presenting a practical examination of both leadership successes and failures.The work challenges readers to think through and discuss specific aspects of leadership, including how and why leadership diversity matters and the ethical challenges presented by the revolving door of the military-industrial complex. Further, leaders responsible for decisions involving war and peace must be able to understand, appreciate, and communicate effectively with everyone they work with and have a repertoire of leadership styles to use depending on context. The book represents an excellent tool for developing such skills, as it uniquely considers leadership through both male and female lenses, along with the experiences and perspectives of multiple military, government, and industry leaders interviewed by the author, making it both relatable and informative.This book will be of much interest to students of gender studies, leadership studies, defense studies, and military studies in general, as well as military and security practitioners.
Keywords: Leadership.; War.; elektronické knihy; electronic books